The Role of Entrepreneurial Leadership to Maintain Company Performance Post Mergers & Acquisition - Purwanto, Agus Sulih; Prijadi, Ruslan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Mergers and acquisitions (M&A deals) are one of the most important events in a company's life cycle and have a significant impact on a company's operations and activities. There are 3 objectives of this research, namely (1) Investigating factors (criteria) of acquiring companies and target companies in the Merger and Acquisition process (2) Investigating leadership characteristics in post-merger and acquisition companies (3) Investigating the role of leadership in achieving company performance that has been achieved. completing the merger and acquisition process in the insurance industry. Researchers used a qualitative approach with a case study method. Based on the level of crystallization of the research question, this research is an exploratory study. This research uses interviews as a primary data source obtained from sources. Qualitative data analysis in this research uses a thematic analysis approach, which is the basic method for conducting qualitative analysis with the help of NVIVO software. Based on the results of research and discussions that have been carried out, the conclusions that can be drawn are (1) factors (criteria) for acquiring companies and target companies in the merger and acquisition process, each of which has its own specificity (2) leadership roles in post-merger and acquisition companies to achieve organizational performance and growth of experience, vision and knowledge; decision making skills; communication skills; team building skills and skills in managing change (3) Key variables for the performance of companies that have completed the merger and acquisition process in the insurance industry are the scope of the merger and acquisition process, the methods used to complete the M&A process and the impact of M&A on performance , employees, work partners and customers.